Data Segmentation Management Infrastructure in a Database Grid - Lourenso, Reinaldo; Kofuji, Sergio Takeo (Anais do International Symposium on Computer Architecture and High Performance Computing (SBAC-PAD), 2006)
This paper sets a data segmentation management infrastructure in a database grid. We verified that the data molding methodologies used do not approach the fragmentation or segmentation of a complex object, as audio, video, etc. This happens because methodologies only take into account the fragmentation of storing tools, in this case relations or classes, and not the stored objects. Our solution using segmentation at the level of attribute/object improved the development of the system which had the necessity of storing elevated sizes documents in a database based on grid